The Brazilian pension reforms under the neoliberal pressure - Ugino, Camila Kimie; Marques, Rosa Maria (Textos & Contextos (Porto Alegre), 2012)
This article deals with the pension reforms done by FHC and Lula, highlighting the arguments used, the changes taken and some of the immediate results after implementation. Despite the attacks on rights, the reforms did not cover the largest interest of neoliberal pension reform, that is, creating a space for massive development of capitalization regime. However, under the concept of Social Security, the reforms virtually emptied its contents, which constitute a serious setback.